Pengembangan Media Multimedia Interaktif Berbasis Adobe Captivate Learning Pada Materi Perubahan Iklim - Fauziah, Fauziah Dwi Wiranti; Hari Utomo, Dwiyono; Sari, Ike (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2022)
This study aims to produce valid/feasible interactive multimedia products as learning media with Adobe Captivate in the application of the learning process. The type of research used is ADDIE model development research, namely analysis, design, development, implementation, and evaluation. The results showed that interactive multimedia learning media using the Adobe Captivate application on climate change materials developed had met the eligibility criteria with an average score of 97.3% of media aspect assessment, and 92.5% of material aspects in the very feasible category. Based on the results and discussion of student responses to interactive multimedia learning media using Adobe Captivate on climate change material, the percentage is 88% is included in the very appropriate category for use in learning